Madagascar's escape from Africa: A high‐resolution plate reconstruction for the Western Somali Basin and implications for supercontinent dispersal. (29th December 2016) - Phethean, Jordan J.J.; Kalnins, Lara M.; van Hunen, Jeroen; Biffi, Paolo G.; Davies, Richard J.; McCaffrey, Ken J.W.
Abstract: Accurate reconstructions of the dispersal of supercontinent blocks are essential for testing continental breakup models. Here, we provide a new plate tectonic reconstruction of the opening of the Western Somali Basin during the breakup of East and West Gondwana. The model is constrained by a new comprehensive set of spreading lineaments, detected in this heavily sedimented basin using a novel technique based on directional derivatives of free‐air gravity anomalies. Vertical gravity gradient and free‐air gravity anomaly maps also enable the detection of extinct mid‐ocean ridge segments, which can be directly compared to several previous ocean magnetic anomaly interpretations of the Western Somali Basin. The best matching interpretations have basin symmetry around the M0 anomaly; these are then used to temporally constrain our plate tectonic reconstruction. The reconstruction supports a tight fit for Gondwana fragments prior to breakup, and predicts that the continent‐ocean transform margin lies along the Rovuma Basin, not along the Davie Fracture Zone (DFZ) as commonly thought. According to our reconstruction, the DFZ represents a major ocean‐ocean fracture zone formed by the coalescence of several smaller fracture zones during evolving plate motions as Madagascar drifted southwards, and offshore Tanzania is an obliquely rifted, rather than transform, margin. New seismic reflection evidence for oceanic crust inboard of the DFZ strongly supports these conclusions. Our results provide important new constraints on the still enigmatic driving mechanism of continental rifting, the nature of the lithosphere in the Western Somali Basin, and its resource potential. Key Points: Filtered directional derivatives of gravity reveal deeply buried fracture zones We present a new tectonic map of the West Somali Basin The Davie Fracture Zone is reinterpreted as an ocean‐ocean fracture zone